Factors Affecting Corporate Social Responsibility (CSR) Disclosure - Oktavianawati, Leny; Wahyuningrum, Indah Fajarini Sri (Accounting Analysis Journal, 2019)
The research aimed to examine the factors affecting CSR disclosure in the annual report of mining companies in Indonesia with indicators of leverage, profitability, board of commissioner size, firm size, and firm status. The population of the research are 46 mining companies listed in the Indonesia Stock Exchange (IDX) which published annual report and / or sustainability report in 2013-2016. This research using purposive sampling with 32 companies consisted of 128 units of analysis. The analytical tool used in this research is multiple linear regression that have previously been analyzed by classical assumption test (normality test, multicollinearity, autocorrelation and heteroscedasticity).The result of this research indicated that leverage have a negative effect on CSRD. While profitability, board of commissioners size, and firm size have a positive effect on CSRD. Meanwhile, the corporate status is not proven to affect CSRD. The conclusion of this research is simultaneous testing shows the influence between independent and dependent variables. Leverage, profitability, board of commissioners size and firm size have significant effect the CSRD. Meanwhile, corporate status findings do not significant affect the CSRD.